The effect of insulator geometrical profile on electric field distributions - Ali A. Salem; R. Abd-Rahman; M. S. Kamarudin; H. Ahmed; N.A. M. Jamail; N. A. Othman; M.F. M. Yousof; M. T. Ishak; S. Al-Ameri (Institute of Advanced Engineering and Science, 2019)
In recent years, silicone rubber (SIR) insulators are use widely on high voltage transmission lines, particularly in heavy polluted environment. The performance of SIR in highly dependent on electric field profile that may lead to other serious problem such as ageing and flashover phenomenon. In this paper, electric field and potential distribution around insulator profile were computed using finite element method approach. Insulator geometrical profile i.e. shed radius, inclination angle, width and length has been varied and analyzed. Simulation results reveal that electric field is greatest at area near to the ground and high voltage terminal. Several recommendations have been proposed on insulator profile in achieving optimized electrical performance of the insulator.